SYNTHESIS OF POLYURETHANE MICROCAPSULE USING INTERFACIAL POLYMERIZATION AS SELF HEALING COATING MATERIAL - Athanasia Amanda Septevani; Evi Triwulandari; Dewi Sondari (Widyariset, 2012)
Polyurethane microcapsule had been made as self healing coating material. Polyurethane microcapsule synthesis had been conducted by interfacial polymerization both spontaneous polymerization and prepolymer polyurethane polymerization using glycerol as renewable palm oil polyol. Based on FTIR-Spectra showed the functional group of polyurethane formed both spontaneous and prepolymer polyurethane polymerization. Polyurethane microcapsule formed was in spherical form. The particle size prepared by spontaneous polimerization was smaller than particle prepared by prepolymer polymerization at range 20,51±12,7 and 139,2±72,3 μm respectively.